Error analysis in solving inferential statistics problems for psychology students - Sulistyani, N (Journal of physics. Conference series, 2019)
Inferential Statistic is a topic in Advanced Statistics lectures which aims to perform various statistical techniques. For psychology students, understanding statistics is not easy, marked by none students who answer correctly all the questions. This research was a descriptive qualitative research with the subject 40 psychology students who took Advanced Statistics in C class. This study aimed to describe forms of errors made by students in solving inferential statistics problems based on Newman analysis stages. The results showed that there were 4 stages of student errors in inferential statistics. 1) Errors in comprehension occurred because students could not read statistics tables or read outputs in the questions. 2) Transformation errors occurred because students were not appropriate in applying/selecting the type of test statistics used or writing hypotheses. 3) Process skill errors occurred because students were less careful in calculating and inability to interpret and interpret the results of calculations. 4) Errors in the encoding stage occurred because students did not answer correctly or inappropriately in drawing conclusions in hypothesis testing. The most common mistakes were errors in process skills especially students couldn't interpret results. This error supported the results of previous studies which concluded that interpreting quantities in statistics was a common problem when students learn statistics.